A comunidade indígena Terena do norte do Mato Grosso:infância, identidade e educação - ZOIA, Alceu (2009)
Our research consists of several subprojects in the project development policies And Public Education of Children in India: history, concepts, projects and practices, Group Study and Research for Children and their Education in Different Contexts (GEPIED), on line search and Professional Teacher Training Program Graduate Education in the Faculty of Education, Federal University of Goias (UFG). This thesis investigates the indigenous Terena community of northern Mato Grosso trying to analyze his childhood and his education. In this sense, we sought to understand how does the process of training these children and what are the concepts of childhood and education that are present in this community. Anchored in the socio-historical approach, we conducted an ethnographic study, documentary and theoretical, where we have the effective participation of diverse community members in developing the survey. For the construction of research data, analysis of documents, bibliography, interviews and visits in the community during the years 2007 to 2009. To understand of social relations that are established in the study group, we present some elements historical constitution of the Terena people, your organization productive and political as well as fundamental aspects of their culture and identity. We seek also to reconstruct this text, the from oral histories and documents of the time, the trajectory of struggles by which these people come to its fixation on Gleba Iriri in Northern Mato Grosso. Having as a match the history of struggles of people, we understand how the educational processes would developing permeated by numerous difficulties in which they passed. Featuring also the great importance that the Terena culture and the need to preserve it take for this group. Through this research was possible to perceive that the community has Terena a constant concern for the education of children and that this is deeply marked cultural values espoused by the group. The child is highly valued and seen as a social and political agent and is deposited in it that are the hopes of keeping their culture, language and traditions. And within these questions, school, community, cultural, bilingual different circumstances and now assumes a prominent place in the villages, as local resistance and reorganization of the indigenous people.